2022
DOI: 10.1021/acsaem.1c03770
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Perovskite Solar Cells with Enhanced Performance Based on a Void-Free Imbedded Interface via a Thin Layer of Mesoporous TiO2

Abstract: The interfacial contacts between the electron transport layer (ETL) and the perovskite film play a crucial role in high-performance perovskite solar cells (PSCs). Herein, we propose a method for depositing a low-temperature-processed mesoporous TiO 2 (mp-TiO 2 ) layer on the SnO 2 ETL (bl-SnO 2 ) with the flexible substrate to enhance the performance of the PSCs. This kind of mesoporous TiO 2 layer can both improve the interfacial contact without voids in the imbedded interface and enhance the mechanical stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…As shown in the SEM image in Figure S8a, the perovskite layer showed good quality with a large grain size of 1370 nm and was pinhole-free. As we know, the large average grain size can effectively reduce defects and grain boundaries, which suppresses nonradiative combinations and improves device performance. , In addition, cross-sectional SEM confirmed that the perovskite showed good crystallinity with a thickness of 671 nm, and all layers of HTM, perovskite, and electron transport material contacted tightly (Figure S8b), which is favorable to enhancing the ability of charge extraction–transfer characteristics . Atomic force microscopy (AFM) was also used to check the film morphology of the pristine perovskite and perovskite/BDT-TA-BTASi on the FTO/TiO 2 substrates (Figure S8c,d).…”
Section: Resultsmentioning
confidence: 97%
“…As shown in the SEM image in Figure S8a, the perovskite layer showed good quality with a large grain size of 1370 nm and was pinhole-free. As we know, the large average grain size can effectively reduce defects and grain boundaries, which suppresses nonradiative combinations and improves device performance. , In addition, cross-sectional SEM confirmed that the perovskite showed good crystallinity with a thickness of 671 nm, and all layers of HTM, perovskite, and electron transport material contacted tightly (Figure S8b), which is favorable to enhancing the ability of charge extraction–transfer characteristics . Atomic force microscopy (AFM) was also used to check the film morphology of the pristine perovskite and perovskite/BDT-TA-BTASi on the FTO/TiO 2 substrates (Figure S8c,d).…”
Section: Resultsmentioning
confidence: 97%
“…Polymer substrate‐based flexible perovskite solar cells. Reproduced with permission from other studies 263–268 …”
Section: Polymer Substrates Based Flexible Emerging Pvsmentioning
confidence: 99%
“…Due to its flexibility, portability, low weight, and ease of integration over small, big, and curved surfaces, developing polymer substrate flexible PSCs technology can be seen as a viable and intriguing field from an application point of view in this situation. [263][264][265][266][267][268] characteristics as well as great flexibility and functional efficiency.…”
Section: Flexible Pscsmentioning
confidence: 99%
“…The regular planar devices (n-i-p) have shown great promise with simple device configuration and demonstrated high-performing devices, but they have certain issues and problems such as high-temperature annealing and expensive organic materials. [2][3][4] These limitations prevent their usage in flexible and multi-junction architectures. [5] Contrarily, the p-i-n device design has certain advantages over their counterparts because charge-selective layers are relatively less absorptive with minimal J-V hysteresis, favorable for flexible substrate and low-temperature device fabrication and thus, can be employed as a top cell in siliconperovskite-tandem devices and for mass production.…”
Section: Introductionmentioning
confidence: 99%
“…Both p‐i‐n and n‐i‐p architectures have been applied to devise potential perovskite devices, where the perovskite active layer is considered to be an intrinsic “i” semiconductor layer, and “p” and “n” here stand for the hole (h + ) and electron (e − ) selective contact layer. The regular planar devices (n‐i‐p) have shown great promise with simple device configuration and demonstrated high‐performing devices, but they have certain issues and problems such as high‐temperature annealing and expensive organic materials [2–4] . These limitations prevent their usage in flexible and multi‐junction architectures [5] .…”
Section: Introductionmentioning
confidence: 99%